Mg2Al4Si5O18: X glass with low-temperature blue light long afterglow and preparation method of Mg2Al4Si5O18: X glass

By adjusting the material composition and structure of Mg2Al4Si5O18:X glass, optimizing the depth and distribution of traps, the limitations of traditional long afterglow luminescent materials in terms of high efficiency and low temperature afterglow, achieving low temperature blue light long afterglow effect, and improving production efficiency and market competitiveness.

CN119461843APending Publication Date: 2025-02-18JIANGNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411634633.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional long afterglow luminescent materials have limitations in terms of high efficiency and low temperature afterglow, and it is difficult to meet the needs of industrial production and market competition.

Method used

By adjusting the material composition and structure of Mg2Al4Si5O18:X glass, the depth and distribution of traps are optimized, and the capture and release efficiency of electrons are improved, thereby improving its long afterglow luminescence characteristics. Specific methods include determining the mathematical relationship between reaction temperature and reaction time, preparing glass using microwave method, and doping rare earth ions such as Eu2+, Sm3+, Tb3+, Pr3+, Er3+, etc.

Benefits of technology

The long afterglow effect of low temperature blue light is achieved, which reduces production costs and complexity, improves production efficiency and market competitiveness of materials, and has stable physical and chemical properties and excellent mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461843A_ABST
    Figure CN119461843A_ABST
Patent Text Reader

Abstract

The invention provides Mg2Al4Si5O18: X glass with low-temperature blue light long afterglow, the chemical expression of the glass is Mg2Al4Si5O18: X, and X is Eu < 2 + >, Sm < 3 + >, Tb < 3 + >, Pr < 3 + > and Er < 3 + >; the preparation method comprises the following steps: (1) determining a mathematical relationship between reaction temperature and reaction time, and obtaining a fitted curve by taking the reaction temperature x as an abscissa and the reaction time y as an ordinate; (2) determining rare earth ions required to be doped, and preparing corresponding raw material mixed powder; and (3) carrying out a reaction according to the predicted reaction time to obtain the Mg2Al4Si5O18: X glass with low-temperature blue light long afterglow. By adjusting the composition and structure of the material, the depth and distribution of traps are optimized, and the electron capture and release efficiency is improved, so that the long afterglow luminescence characteristic of the Mg2Al4Si5O18: X glass is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic luminescent materials, and in particular to a low-temperature blue light long afterglow Mg2Al4Si5O 18 :X glass and its preparation method. Background Art

[0002] The phenomenon of long afterglow luminescence is a fascinating optical property. Its core mechanism lies in the trap structures present in the matrix material that can capture electrons. These trapped electrons are slowly released in the form of photons at a later time, resulting in a sustained luminescence effect. This phenomenon can be observed in a variety of materials, including but not limited to organic polymers, inorganic minerals, and metal-organic frameworks (MOFs). These materials emit light over a wide range of spectra, from ultraviolet to near-infrared light, and the duration of afterglow varies significantly, ranging from a few seconds to several days. However, although traditional long afterglow luminescent materials such as silicates, aluminates, gallates, and germanates perform well in some aspects, they still have limitations in terms of high efficiency and low-temperature afterglow. Summary of the invention

[0003] The present invention provides a low-temperature blue light long afterglow Mg2Al4Si5O 18 :X glass and its preparation method are used to solve the above problems.

[0004] The purpose of the present invention is to provide a low-temperature blue light long afterglow Mg2Al4Si5O 18 :X glass, its chemical formula is: Mg2Al4Si5O 18 :X,X=Eu 2+ ,Sm 3+ ,Tb 3+ ,Pr 3+ ,Er 3+ .

[0005] Another object of the present invention is to provide a low-temperature blue light long afterglow Mg2Al4Si5O 18 :X glass preparation method, comprising the following steps:

[0006] Step (a) Determine the mathematical relationship between reaction temperature and reaction time

[0007] MgO, Al2O3, and SiO2 were mixed in a mass ratio of 1.1612:2.039:3.605, the weighed raw materials were put into a mortar, and ground to obtain a raw material mixed powder for preparing a matrix;

[0008] The mixed powder of the raw materials of the parent is placed in a reaction container as a reactant, and then the reaction container is placed in a microwave reaction device; the microwave reaction device is set to 100% power, and a time point is recorded every 2 minutes within the range of 1 to 25 minutes. When the reaction reaches each time point, the core temperature of the reaction container is measured and recorded as the reaction temperature;

[0009] With reaction temperature x as the abscissa and reaction time y as the ordinate, a fitting curve is obtained, and the expression of the fitting curve is: y=0.16904×exp(x / 181.79415)+0.63894;

[0010] Step (ii): determine the rare earth ions to be doped and prepare the corresponding raw material mixed powder

[0011] Select Eu 2+ ,Sm 3+ ,Tb 3+ ,Pr 3+ ,Er 3+ As one of the doping ions, prepare MgO, Al2O3, SiO2 and oxides corresponding to the doped rare earth ions, mix them according to the mass ratio of 1.1612:2.039:3.605:0.0500, grind the weighed raw materials to obtain raw material mixed powder;

[0012] Step (iii): react according to the predicted reaction time

[0013] According to the lowest phase transition temperatures of MgO, Al2O3, SiO2 and the oxides corresponding to the doping ions, the average value is calculated as the reaction temperature during the microwave preparation, and the corresponding reaction time is predicted according to the fitting curve obtained in step (i);

[0014] The raw material mixed powder obtained in step (ii) is spread flat and placed in the middle and lower layer of the raw material crucible, and the raw material crucible is embedded in the carbon powder crucible, and then the carbon powder crucible is placed in the cavity formed by the heat-resistant brick body and the brick bottom, and the brick cover is closed and placed in a reaction microwave oven, and the carbon powder crucible is filled with activated carbon; react according to the predicted reaction time, and after the reaction is completed, the low-temperature blue light long afterglow Mg2Al4Si5O 18 :XGlass.

[0015] As a further preference of the above scheme:

[0016] In the step (a), the fitting curve is obtained by using the single exponential fitting method of nonlinear fitting in Origin.

[0017] As a further preference of the above scheme:

[0018] In the step (ii), when the doped ion is Eu 2+When the doped ion is Sm 3+ When the doped ion is Tb 3+ When the doped ion is Pr 3+ When the doped ion is Er 3+ When , the corresponding oxide is Er2O3.

[0019] As a further preference of the above scheme:

[0020] The mesh size of the activated carbon particles in the step (iii) is 100-200 meshes.

[0021] As a further preference of the above scheme:

[0022] In the step (iii), the mass ratio of the raw material mixed powder to the activated carbon is 1:6.

[0023] As a further preference of the above scheme:

[0024] In the step (iii), the reaction is carried out at a power of 600-1000 W according to the predicted reaction time.

[0025] The beneficial effects of the present invention are as follows: by adjusting the composition and structure of the material, optimizing the depth and distribution of the trap, and improving the efficiency of electron capture and release, the Mg2Al4Si5O 18 :X glass has long afterglow luminescence characteristics, as follows:

[0026] (1) Mg2Al4Si5O prepared by the present invention 18 :X glass raw materials are extensive and economical. The raw materials of this glass are abundant, easy to obtain, and low in cost, making it very suitable for industrial production. This not only reduces production costs, but also improves production efficiency, making Mg2Al4Si5O 18 :X glass has obvious price advantages in market competition.

[0027] (2) Mg2Al4Si5O prepared by the method of the present invention 18 :X glass, the entire preparation process does not require special reducing atmosphere protection measures, which reduces the production complexity and further improves the production efficiency. This simple and efficient preparation process is Mg2Al4Si5O 18 :X The wide application of glass provides a strong guarantee.

[0028] (3) Mg2Al4Si5O prepared by the present invention 18:X glass also has stable physical and chemical properties, high transparency and excellent mechanical strength. These characteristics make Mg2Al4Si5O 18 :X glass can maintain its stable performance in various harsh environments while meeting the needs of optical and mechanical applications.

[0029] (4) Mg2Al4Si5O prepared by the present invention 18 :X glass also exhibits a long afterglow time and persistent luminescence characteristics. Under 365nm excitation, the luminescence intensity of the material changes very little from low temperature (-120℃) to high temperature (230℃), especially in the period from low temperature to room temperature, the intensity change rate is only 0.3%. This long afterglow luminescence characteristic makes Mg2Al4Si5O 18 :X glass has broad application prospects in lighting, display, signage and other fields.

[0030] (5) Compared with the traditional high temperature method, the microwave method is used to prepare Mg2Al4Si5O 18 :X glass can be greatly improved, the reaction time of the microwave method can be significantly reduced, and the method of the present invention is more efficient. However, it was found during the research process of the present invention that the microwave method cannot obtain the Mg2Al4Si5O 18 :X glass reaction time, usually only based on experience to set the reaction time will be too short or too long, too short reaction time will lead to the sample can not be synthesized, too long reaction time will lead to the complete evaporation of the sample. 18 :X, the concentration of doping ions in the luminescent center is 1%, and the amount used is small, so the method of the present invention can be used to prepare the matrix Mg2Al4Si5O 18 The mathematical relationship between the core temperature and reaction time can be used to predict the microwave preparation of Mg2Al4Si5O when the reaction temperature x is known. 18 Therefore, the preparation method of the present invention also solves the problem of using microwave method to prepare Mg2Al4Si5O 18 : When using X glass, there are problems such as the sample cannot be synthesized due to the reaction time being too short, and the sample completely evaporates due to the reaction time being too high. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0032] Figure 1 The photographs of the material prepared in Inventive Example 1 under different excitation sources;

[0033] Figure 2 These are photos of the material prepared in Inventive Example 2 under different excitation sources;

[0034] Figure 3 These are photos of the material prepared in Example 3 of the present invention under different excitation sources;

[0035] Figure 4 This is the X-ray diffraction spectrum of the material prepared in Example 3 of the present invention;

[0036] Figure 5 The best excitation and best emission spectra of the material prepared in Example 3 of the present invention;

[0037] Figure 6 This is an afterglow photograph of the material prepared in Example 3 of the present invention;

[0038] Figure 7 The long afterglow excitation spectrum of the material prepared in Example 3 of the present invention;

[0039] Figure 8 The temperature dependence spectrum of the material prepared in Example 3 of the present invention;

[0040] Fig. 9 This is a low temperature photograph of the material prepared in Example 3 of the present invention;

[0041] Fig.10 This is a low-temperature photomultiplier tube signal collection curve of the material prepared in Example 3 of the present invention;

[0042] Fig.11 These are photos of the material prepared in Example 4 of the present invention under different excitation sources;

[0043] Fig.12 X-ray diffraction spectrum of the material prepared in Example 4 of the present invention

[0044] Fig.13 The best excitation and best emission spectra of the material prepared in Example 4 of the present invention;

[0045] Fig.14 These are photos of the material prepared in Example 5 of the present invention under different excitation sources;

[0046] Fig.15 The X-ray diffraction spectrum of the material prepared in Example 5 of the present invention;

[0047] Fig.16 The best excitation and best emission spectra of the material prepared in Example 5 of the present invention;

[0048] Fig.17 These are photos of the material prepared in Example 6 of the present invention under different excitation sources;

[0049] Fig.18Photographs of the materials prepared in Example 7 of the present invention under different excitation sources. Detailed implementation mode

[0050] The present invention will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and not to limit the scope of the present invention.

[0051] The present invention provides a Mg2Al4Si5O 18 :X glass, and the chemical formula is: Mg2Al4Si5O 18 :X, X = Eu 2+ , Sm 3+ , Tb 3+ , Pr 3+ , Er 3+ . The thermal imager used in the specific implementation mode of the present invention is: Fluke infrared imager (Ti480 Pro, USA), and the microwave reaction device is: Koyamaki / Takano Maki 30MX67. It should be noted that the method of the present invention is not limited to the foregoing thermal imager and microwave oven, and is also applicable to other types and brands of thermal imager and microwave oven equipment.

[0052] Example 1

[0053] In this Example 1, a preparation method of Mg2Al4Si5O 18 :Eu 2+ glass with low-temperature long afterglow properties is provided, and the method includes the following steps:

[0054] Step (1), determining the mathematical relationship between the reaction temperature and the reaction time for preparing the matrix

[0055] (1), Mix MgO, Al2O3, and SiO2 according to a mass ratio of 1.1612:2.039:3.605. Put the weighed raw materials into a mortar and grind to obtain a raw material mixture powder for preparing the matrix;

[0056] (2), Prepare a high-temperature resistant reaction vessel that can withstand high temperatures and whose temperature can be measured using a thermal imager. Place the raw material mixture powder of the foregoing matrix as a reactant in the reaction vessel, and then put the reaction vessel into a microwave reaction device;

[0057] (3), Set the power of the microwave reaction device to 100%; within the time range of 1 to 25 minutes, record a time point every 2 minutes. When the reaction reaches each time point, use a thermal imager to measure the core temperature of the reaction vessel, which is recorded as the reaction temperature;

[0058] (4) Data collection: At each time point, record the core reaction temperature of the reaction vessel in degrees Celsius, and obtain the reaction temperature corresponding to the reaction time in minutes;

[0059] (5) Data processing and analysis: The collected data were further analyzed using statistical software. The reaction temperature x was taken as the horizontal axis and the reaction time y was taken as the vertical axis. The fitting curve was obtained using the single exponential fitting method of nonlinear fitting in Origin. The expression of the fitting curve was: y = 0.16904 × exp(x / 181.79415) + 0.63894;

[0060] According to the above relationship, the matrix Mg2Al4Si5O 18 The mathematical relationship between the core temperature and the reaction time is obtained, and the microwave method is used to predict the preparation of Mg2Al4Si5O 18 :Eu 2+ The reaction time of the glass is y;

[0061] Step (ii): prepare the corresponding raw material mixed powder according to the rare earth ions to be doped

[0062] Prepare MgO, Al2O3, SiO2 and Eu2O, mix them according to the mass ratio of 1.1612:2.039:3.605:0.0500, put the weighed raw materials into a mortar, grind the raw materials to obtain raw material mixed powder; put them into an agate mortar, grind the raw materials again, and prepare Mg2Al4Si5O 18 :Eu 2+ Raw material mixed powder;

[0063] Step (iii): react according to the predicted reaction time to obtain luminescent afterglow glass

[0064] According to the minimum phase transition temperatures required for MgO, Al2O3, SiO2 and Eu2O3, which are 1500℃, 1200℃, 5.5℃ and 822℃ respectively, their average values ​​are calculated as the Mg2Al4Si5O 18 :Eu 2+ The reaction temperature is calculated to be 882°C. According to the fitting curve obtained in step (a), the corresponding reaction time is predicted to be 22 min.

[0065] The raw material mixed powder obtained in step (ii) is spread flat and placed in the middle and lower layer of the raw material crucible, and the raw material crucible is embedded in the half of the carbon powder crucible; in this embodiment, the preferred reaction set is made of ultra-high temperature heat-resistant material, including a brick body, a brick bottom and a brick cover covering the top opening of the brick body, the brick body is a cylindrical structure with a top and a top opening, the brick bottom is against the bottom opening of the brick body, the brick body and the brick bottom form a reaction cavity, the aforementioned carbon powder crucible is placed in the cavity formed by the brick body and the brick bottom, and then the brick cover is closed, and the entire reaction set is placed in a microwave reaction device; wherein the aforementioned carbon powder crucible is filled with activated carbon, the mesh number of the activated carbon particles is 100 mesh, and the mass ratio of the raw material mixed powder to the activated carbon is 1:6; at a power of 600W, the reaction is carried out according to the predicted reaction time of 22min, and after the reaction is completed, the glass luminescent afterglow material Mg2Al4Si5O is obtained after natural cooling. 18 :Eu 2+ Glass.

[0066] The method of Example 1 is based on the preparation by microwave method. On the one hand, step (i) is designed to obtain a fitting curve to determine the mathematical relationship between the reaction temperature and reaction time for preparing the matrix, so that the reaction time can be predicted by the reaction temperature. On the other hand, since the microwave method is used to prepare Mg2Al4Si5O 18 :X, the luminescent center is doped with ions Eu 2+ The concentration is 1%, the amount used is small, and the effect on the reaction temperature is negligible, so in the preparation of Mg2Al4Si5O 18 :Eu 2+ When the reaction temperature x is known, the microwave method for preparing Mg2Al4Si5O 18 :Eu 2+ Therefore, the preparation method of the present invention also solves the problem of using microwave method to prepare Mg2Al4Si5O 18 When using X glass, since it is impossible to get the accurate reaction time in advance, there are problems such as the reaction time is too short and the sample cannot be synthesized, or the reaction time is too long and the sample evaporates completely.

[0067] Example 2

[0068] In this embodiment 2, a Mg2Al4Si5O 18 :Eu 2+ The method for preparing glass comprises the following steps:

[0069] Step (a) determining the mathematical relationship between the reaction temperature and reaction time for preparing the matrix

[0070] (1) Mix MgO, Al2O3 and SiO2 in a mass ratio of 1.1612:2.039:3.605, put the weighed raw materials into a mortar, and grind them to obtain a raw material mixed powder for preparing a matrix;

[0071] (2) preparing a high temperature resistant reaction container which can withstand high temperatures and can be measured using a thermal imager, placing the above-mentioned mixed raw material powder of the precursor as a reactant in the reaction container, and then placing the reaction container in a microwave reaction device;

[0072] (3) Setting the microwave reaction device to 100% power; recording a time point every 2 minutes within a time range of 1 to 25 minutes; using a thermal imager to measure the core temperature of the reaction vessel at each time point, and recording it as the reaction temperature;

[0073] (4) Data collection: At each time point, record the core reaction temperature of the reaction vessel in degrees Celsius, and obtain the reaction temperature corresponding to the reaction time in minutes;

[0074] (5) Data processing and analysis: The collected data were further analyzed using statistical software. The reaction temperature x was taken as the horizontal axis and the reaction time y was taken as the vertical axis. The fitting curve was obtained using the single exponential fitting method of nonlinear fitting in Origin. The expression of the fitting curve was: y = 0.16904 × exp(x / 181.79415) + 0.63894;

[0075] According to the above relationship, the matrix Mg2Al4Si5O 18 The mathematical relationship between the core temperature and the reaction time is obtained, and the microwave method is used to predict the preparation of Mg2Al4Si5O 18 :Eu 2+ The reaction time of the glass is y;

[0076] Step (ii): prepare the corresponding raw material mixed powder according to the rare earth ions to be doped

[0077] Prepare MgO, Al2O3, SiO2 and Eu2O, mix them according to the mass ratio of 1.1612:2.039:3.605:0.0500, put the weighed raw materials into a mortar, grind the raw materials to obtain raw material mixed powder; put them into an agate mortar, grind the raw materials again, and prepare Mg2Al4Si5O 18 :Eu 2+ Raw material mixed powder;

[0078] Step (iii): react according to the predicted reaction time to obtain luminescent afterglow glass

[0079] According to the minimum phase transition temperatures required for MgO, Al2O3, SiO2 and Eu2O3, which are 1500℃, 1200℃, 5.5℃ and 822℃ respectively, their average values ​​are calculated as the Mg2Al4Si5O 18 :Eu 2+ The reaction temperature is calculated to be 882°C. According to the fitting curve obtained in step (a), the corresponding reaction time is predicted to be 22 min.

[0080] The raw material mixed powder obtained in step (ii) is spread flat and placed in the middle and lower layer of the raw material crucible, and the raw material crucible is embedded in the half of the carbon powder crucible, and then the carbon powder crucible is placed in the cavity formed by the ultra-high temperature heat-resistant brick body and the brick bottom, and then the brick cover is closed, and finally the entire reaction set is placed in the microwave reaction device; the carbon powder crucible is filled with activated carbon, the mesh number of the activated carbon particles is 150 mesh, and the mass ratio of the raw material mixed powder to the activated carbon is 1:6; at a power of 800 W, the reaction is carried out according to the predicted reaction time of 22 minutes, and after the reaction is completed, the glass luminescent afterglow material Mg2Al4Si5O is obtained after natural cooling. 18 :Eu 2+ Glass.

[0081] Example 3

[0082] In this embodiment 3, a Mg2Al4Si5O 18 :Eu 2+ The method for preparing glass comprises the following steps:

[0083] Step (a) determining the mathematical relationship between the reaction temperature and reaction time for preparing the matrix

[0084] (1) Mix MgO, Al2O3 and SiO2 in a mass ratio of 1.1612:2.039:3.605, put the weighed raw materials into a mortar, and grind them to obtain a raw material mixed powder for preparing a matrix;

[0085] (2) preparing a high temperature resistant reaction container which can withstand high temperatures and can be measured using a thermal imager, placing the above-mentioned mixed raw material powder of the precursor as a reactant in the reaction container, and then placing the reaction container in a microwave reaction device;

[0086] (3) Setting the microwave reaction device to 100% power; recording a time point every 2 minutes within a time range of 1 to 25 minutes; using a thermal imager to measure the core temperature of the reaction vessel at each time point, and recording it as the reaction temperature;

[0087] (4) Data collection: At each time point, record the core reaction temperature of the reaction vessel in degrees Celsius, and obtain the reaction temperature corresponding to the reaction time in minutes;

[0088] (5) Data processing and analysis: The collected data were further analyzed using statistical software. The reaction temperature x was taken as the horizontal axis and the reaction time y was taken as the vertical axis. The fitting curve was obtained using the single exponential fitting method of nonlinear fitting in Origin. The expression of the fitting curve was: y = 0.16904 × exp(x / 181.79415) + 0.63894;

[0089] According to the above relationship, the matrix Mg2Al4Si5O 18 The mathematical relationship between the core temperature and the reaction time is obtained, and the microwave method is used to predict the preparation of Mg2Al4Si5O 18 :Eu 2+ The reaction time of the glass is y;

[0090] Step (ii): prepare the corresponding raw material mixed powder according to the rare earth ions to be doped

[0091] Prepare MgO, Al2O3, SiO2 and Eu2O, mix them according to the mass ratio of 1.1612:2.039:3.605:0.0500, put the weighed raw materials into a mortar, grind the raw materials to obtain raw material mixed powder; put them into an agate mortar, grind the raw materials again, and prepare Mg2Al4Si5O 18 :Eu 2+ Raw material mixed powder;

[0092] Step (iii): react according to the predicted reaction time to obtain luminescent afterglow glass

[0093] According to the minimum phase transition temperatures required for MgO, Al2O3, SiO2 and Eu2O3, which are 1500℃, 1200℃, 5.5℃ and 822℃ respectively, their average values ​​are calculated as the Mg2Al4Si5O 18 :Eu 2+ The reaction temperature is calculated to be 882°C. According to the fitting curve obtained in step (a), the corresponding reaction time is predicted to be 22 min.

[0094] The raw material mixed powder obtained in step (ii) is spread flat and placed in the middle and lower layer of the raw material crucible, and the raw material crucible is embedded in the half of the carbon powder crucible, and then the carbon powder crucible is placed in the cavity formed by the ultra-high temperature heat-resistant brick body and the brick bottom, and then the brick cover is closed, and finally the entire reaction set is placed in a microwave reaction device; the carbon powder crucible is filled with activated carbon, the activated carbon particle size is 200 mesh, and the mass ratio of the raw material mixed powder to the activated carbon is 1:6; at a power of 1000W, the reaction is carried out according to the predicted reaction time of 22min, and after the reaction is completed, the glass luminescent afterglow material Mg2Al4Si5O is obtained after natural cooling. 18 :Eu 2+ Glass.

[0095] Example 4

[0096] In this embodiment 4, a Mg2Al4Si5O 18 :Sm 3+ The method for preparing glass comprises the following steps:

[0097] Step (a) determining the mathematical relationship between the reaction temperature and reaction time for preparing the matrix

[0098] (1) Mix MgO, Al2O3 and SiO2 in a mass ratio of 1.1612:2.039:3.605, put the weighed raw materials into a mortar, and grind them to obtain a raw material mixed powder for preparing a matrix;

[0099] (2) preparing a high temperature resistant reaction container which can withstand high temperatures and can be measured using a thermal imager, placing the above-mentioned mixed raw material powder of the precursor as a reactant in the reaction container, and then placing the reaction container in a microwave reaction device;

[0100] (3) Setting the microwave reaction device to 100% power; recording a time point every 2 minutes within a time range of 1 to 25 minutes; using a thermal imager to measure the core temperature of the reaction vessel at each time point, and recording it as the reaction temperature;

[0101] (4) Data collection: At each time point, record the core reaction temperature of the reaction vessel in degrees Celsius, and obtain the reaction temperature corresponding to the reaction time in minutes;

[0102] (5) Data processing and analysis: The collected data were further analyzed using statistical software. The reaction temperature x was taken as the horizontal axis and the reaction time y was taken as the vertical axis. The fitting curve was obtained using the single exponential fitting method of nonlinear fitting in Origin. The expression of the fitting curve was: y = 0.16904 × exp(x / 181.79415) + 0.63894;

[0103] According to the above relationship, the matrix Mg2Al4Si5O 18 The mathematical relationship between the core temperature and the reaction time is obtained, and the microwave method is used to predict the preparation of Mg2Al4Si5O 18 :Sm 3+ The reaction time of the glass is y;

[0104] Step (ii): prepare the corresponding raw material mixed powder according to the rare earth ions to be doped

[0105] Prepare MgO, Al2O3, SiO2 and Sm2O3, mix them according to the mass ratio of 1.1612:2.039:3.605:0.0500, put the weighed raw materials into a mortar, grind the raw materials to obtain raw material mixed powder; put them into an agate mortar, grind the raw materials again, and prepare Mg2Al4Si5O 18 :Sm 3+ Raw material mixed powder;

[0106] Step (iii): react according to the predicted reaction time to obtain luminescent afterglow glass

[0107] According to the minimum phase transition temperatures required for MgO, Al2O3, SiO2 and Sm2O3, which are 1500℃, 1200℃, 5.5℃ and 1072℃ respectively, their average values ​​are calculated as the Mg2Al4Si5O 18 :Sm 3+ The reaction temperature is calculated to be 944°C. According to the fitting curve obtained in step (a), the corresponding reaction time is predicted to be 31min.

[0108] The raw material mixed powder obtained in step (ii) is spread flat and placed in the middle and lower layer of the raw material crucible, and the raw material crucible is embedded in the half of the carbon powder crucible, and then the carbon powder crucible is placed in the cavity formed by the ultra-high temperature heat-resistant brick body and the brick bottom, and then the brick cover is closed, and finally the entire reaction set is placed in a microwave reaction device; the carbon powder crucible is filled with activated carbon, the mesh number of the activated carbon particles is 200 mesh, and the mass ratio of the raw material mixed powder to the activated carbon is 1:6; at a power of 1000 W, the reaction is carried out according to the predicted reaction time of 31 minutes, and after the reaction is completed, the glass luminescent afterglow material Mg2Al4Si5O is obtained after natural cooling. 18 :Sm 3+ Glass.

[0109] Example 5

[0110] In this embodiment 5, a Mg2Al4Si5O 18 :Tb 3+ The method for preparing glass comprises the following steps:

[0111] Step (a) determining the mathematical relationship between the reaction temperature and reaction time for preparing the matrix

[0112] (1) Mix MgO, Al2O3 and SiO2 in a mass ratio of 1.1612:2.039:3.605, put the weighed raw materials into a mortar, and grind them to obtain a raw material mixed powder for preparing a matrix;

[0113] (2) preparing a high temperature resistant reaction container which can withstand high temperatures and can be measured using a thermal imager, placing the above-mentioned mixed raw material powder of the precursor as a reactant in the reaction container, and then placing the reaction container in a microwave reaction device;

[0114] (3) Setting the microwave reaction device to 100% power; recording a time point every 2 minutes within a time range of 1 to 25 minutes; using a thermal imager to measure the core temperature of the reaction vessel at each time point, and recording it as the reaction temperature;

[0115] (4) Data collection: At each time point, record the core reaction temperature of the reaction vessel in degrees Celsius, and obtain the reaction temperature corresponding to the reaction time in minutes;

[0116] (5) Data processing and analysis: The collected data were further analyzed using statistical software. The reaction temperature x was taken as the horizontal axis and the reaction time y was taken as the vertical axis. The fitting curve was obtained using the single exponential fitting method of nonlinear fitting in Origin. The expression of the fitting curve was: y = 0.16904 × exp(x / 181.79415) + 0.63894;

[0117] According to the above relationship, the matrix Mg2Al4Si5O 18 The mathematical relationship between the core temperature and the reaction time is obtained, and the microwave method is used to predict the preparation of Mg2Al4Si5O 18 :Tb 3+ The reaction time of the glass is y;

[0118] Step (ii): prepare the corresponding raw material mixed powder according to the rare earth ions to be doped

[0119] Prepare MgO, Al2O3, SiO2 and Tb4O7, mix them according to the mass ratio of 1.1612:2.039:3.605:0.0500, put the weighed raw materials into a mortar, grind the raw materials to obtain raw material mixed powder; put them into an agate mortar, grind the raw materials again, and prepare Mg2Al4Si5O 18 :Tb 3+ Raw material mixed powder;

[0120] Step (iii): react according to the predicted reaction time to obtain luminescent afterglow glass

[0121] According to the minimum phase transition temperatures required for MgO, Al2O3, SiO2 and Tb4O7, which are 1500℃, 1200℃, 5.5℃ and 1289℃ respectively, their average values ​​are calculated as the average phase transition temperature of Mg2Al4Si5O 18 :Tb 3+ The reaction temperature is calculated to be 998°C. According to the fitting curve obtained in step (i), the corresponding reaction time is predicted to be 42min.

[0122] The raw material mixed powder obtained in step (ii) is spread flat and placed in the middle and lower layer of the raw material crucible, and the raw material crucible is embedded in the half of the carbon powder crucible, and then the carbon powder crucible is placed in the cavity formed by the ultra-high temperature heat-resistant brick body and the brick bottom, and then the brick cover is closed, and finally the entire reaction set is placed in a microwave reaction device; the carbon powder crucible is filled with activated carbon, the mesh number of the activated carbon particles is 200 mesh, and the mass ratio of the raw material mixed powder to the activated carbon is 1:6; at a power of 1000 W, the reaction is carried out according to the predicted reaction time of 42 minutes, and after the reaction is completed, the glass luminescent afterglow material Mg2Al4Si5O is obtained after natural cooling. 18 :Tb 3+ Glass.

[0123] Example 6

[0124] In this embodiment 6, a Mg2Al4Si5O 18 :Pr 3+ The method for preparing glass comprises the following steps:

[0125] Step (a) determining the mathematical relationship between the reaction temperature and reaction time for preparing the matrix

[0126] (1) Mix MgO, Al2O3 and SiO2 in a mass ratio of 1.1612:2.039:3.605, put the weighed raw materials into a mortar, and grind them to obtain a raw material mixed powder for preparing a matrix;

[0127] (2) preparing a high temperature resistant reaction container which can withstand high temperatures and can be measured using a thermal imager, placing the above-mentioned mixed raw material powder of the precursor as a reactant in the reaction container, and then placing the reaction container in a microwave reaction device;

[0128] (3) Setting the microwave reaction device to 100% power; recording a time point every 2 minutes within a time range of 1 to 25 minutes; using a thermal imager to measure the core temperature of the reaction vessel at each time point, and recording it as the reaction temperature;

[0129] (4) Data collection: At each time point, record the core reaction temperature of the reaction vessel in degrees Celsius, and obtain the reaction temperature corresponding to the reaction time in minutes;

[0130] (5) Data processing and analysis: The collected data were further analyzed using statistical software. The reaction temperature x was taken as the horizontal axis and the reaction time y was taken as the vertical axis. The fitting curve was obtained using the single exponential fitting method of nonlinear fitting in Origin. The expression of the fitting curve was: y = 0.16904 × exp(x / 181.79415) + 0.63894;

[0131] According to the above relationship, the matrix Mg2Al4Si5O 18 The mathematical relationship between the core temperature and the reaction time is obtained, and the microwave method is used to predict the preparation of Mg2Al4Si5O 18 :Pr 3+ The reaction time of the glass is y;

[0132] Step (ii): prepare the corresponding raw material mixed powder according to the rare earth ions to be doped

[0133] Prepare MgO, Al2O3, SiO2 and Pr2O3, mix them according to the mass ratio of 1.1612:2.039:3.605:0.0500, put the weighed raw materials into a mortar, grind the raw materials to obtain raw material mixed powder; put them into an agate mortar, grind the raw materials again, and prepare Mg2Al4Si5O 18 :Pr 3+ Raw material mixed powder;

[0134] Step (iii): react according to the predicted reaction time to obtain luminescent afterglow glass

[0135] According to the minimum phase transition temperatures required for MgO, Al2O3, SiO2 and Pr2O3, which are 1500℃, 1200℃, 5.5℃ and 931℃ respectively, their average values ​​are calculated as the Mg2Al4Si5O 18 :Pr 3+ The reaction temperature is calculated to be 909°C. According to the fitting curve obtained in step (a), the corresponding reaction time is predicted to be 25min.

[0136] The raw material mixed powder obtained in step (ii) is spread flat and placed in the middle and lower layer of the raw material crucible, and the raw material crucible is embedded in the half of the carbon powder crucible, and then the carbon powder crucible is placed in the cavity formed by the ultra-high temperature heat-resistant brick body and the brick bottom, and then the brick cover is closed, and finally the entire reaction set is placed in a microwave reaction device; the carbon powder crucible is filled with activated carbon, the mesh number of the activated carbon particles is 200 mesh, and the mass ratio of the raw material mixed powder to the activated carbon is 1:6; at a power of 1000 W, the reaction is carried out according to the predicted reaction time of 25 minutes, and after the reaction is completed, the glass luminescent afterglow material Mg2Al4Si5O is obtained after natural cooling. 18 :Pr 3+ Glass.

[0137] Example 7

[0138] In this embodiment 7, a Mg2Al4Si5O 18 :Er 3+ The method for preparing glass comprises the following steps:

[0139] Step (a) determining the mathematical relationship between the reaction temperature and reaction time for preparing the matrix

[0140] (1) Mix MgO, Al2O3 and SiO2 in a mass ratio of 1.1612:2.039:3.605, put the weighed raw materials into a mortar, and grind them to obtain a raw material mixed powder for preparing a matrix;

[0141] (2) preparing a high temperature resistant reaction container which can withstand high temperatures and can be measured using a thermal imager, placing the above-mentioned mixed raw material powder of the precursor as a reactant in the reaction container, and then placing the reaction container in a microwave reaction device;

[0142] (3) Setting the microwave reaction device to 100% power; recording a time point every 2 minutes within a time range of 1 to 25 minutes; using a thermal imager to measure the core temperature of the reaction vessel at each time point, and recording it as the reaction temperature;

[0143] (4) Data collection: At each time point, record the core reaction temperature of the reaction vessel in degrees Celsius, and obtain the reaction temperature corresponding to the reaction time in minutes;

[0144] (5) Data processing and analysis: The collected data were further analyzed using statistical software. The reaction temperature x was taken as the horizontal axis and the reaction time y was taken as the vertical axis. The fitting curve was obtained using the single exponential fitting method of nonlinear fitting in Origin. The expression of the fitting curve was: y = 0.16904 × exp(x / 181.79415) + 0.63894;

[0145] According to the above relationship, the matrix Mg2Al4Si5O 18 The mathematical relationship between the core temperature and the reaction time is obtained, and the microwave method is used to predict the preparation of Mg2Al4Si5O 18 :Er 3+ The reaction time of the glass is y;

[0146] Step (ii): prepare the corresponding raw material mixed powder according to the rare earth ions to be doped

[0147] Prepare MgO, Al2O3, SiO2 and Er2O3, mix them according to the mass ratio of 1.1612:2.039:3.605:0.0500, put the weighed raw materials into a mortar, grind the raw materials to obtain raw material mixed powder; put them into an agate mortar, grind the raw materials again, and prepare Mg2Al4Si5O 18 :Er 3+ Raw material mixed powder;

[0148] Step (iii): react according to the predicted reaction time to obtain luminescent afterglow glass

[0149] According to the minimum phase transition temperatures required for MgO, Al2O3, SiO2 and Er2O3, which are 1500℃, 1200℃, 5.5℃ and 1300℃ respectively, their average values ​​are calculated as the Mg2Al4Si5O 18 :Er 3+ The reaction temperature is calculated to be 1001°C, and the corresponding reaction time is predicted to be 43min according to the fitting curve obtained in step (a);

[0150] The raw material mixed powder obtained in step (ii) is spread flat and placed in the middle and lower layer of the raw material crucible, and the raw material crucible is embedded in the half of the carbon powder crucible, and then the carbon powder crucible is placed in the cavity formed by the ultra-high temperature heat-resistant brick body and the brick bottom, and then the brick cover is closed, and finally the entire reaction set is placed in a microwave reaction device; the carbon powder crucible is filled with activated carbon, the mesh number of the activated carbon particles is 200 mesh, and the mass ratio of the raw material mixed powder to the activated carbon is 1:6; at a power of 1000 W, the reaction is carried out according to the predicted reaction time of 43 minutes, and after the reaction is completed, the glass luminescent afterglow material Mg2Al4Si5O is obtained after natural cooling. 18 :Er 3+ Glass.

[0151] Experimental analysis

[0152] Experiment 1: The materials obtained in the examples were analyzed using an X-ray diffractometer. The results are as follows: Figure 4 , 12As shown in Figure 15, it can be seen that the material Mg2Al4Si5O prepared by the present invention reacts for 30 minutes at a power of 1000W. 18 The characteristic peak of the diffraction spectrum of X gradually disappears, indicating that the material becomes vitrified at a certain power and reaction time. XRD confirms that the Mg2Al4Si5O prepared by the present invention 18 :The successful synthesis of X glass.

[0153] Experiment 2: The material prepared in Example 3 was excited with different excitation sources, and photographed using a mobile phone in normal mode (not night mode) to obtain Figure 3 From this, we can see that under the excitation of 254nm ultraviolet light, the whole emits blue light, which is weak; under the excitation of 310nm ultraviolet light, the whole also emits blue light, which is weak; under the excitation of 365nm light, the whole emits blue-white light, which is very obvious.

[0154] Experiment 3: The material prepared in Example 3 was subjected to spectral testing to obtain excitation and emission spectra. The results are as follows: Figure 5 As shown in the figure, it can be seen that the material Mg2Al4Si5O prepared by the present invention 18 :Eu 2+ There are different characteristic peaks under different wavelengths of excitation light. Under the excitation of 349nm ultraviolet light, the spectrum has a narrow peak at 439nm, which is Eu 2+ The material emits blue light due to the characteristic emission peak.

[0155] Experiment 4: After the material prepared in Example 3 was excited by a 365nm ultraviolet lamp for 60s, a long blue afterglow phenomenon was observed in the dark environment. The afterglow photo is shown in Figure 6 shown.

[0156] Experiment 5: The material prepared in Example 3 was subjected to spectrum testing to obtain a long afterglow excitation spectrum. The results are as follows: Figure 7 As shown in the figure, it can be seen that the material Mg2Al4Si5O prepared by the present invention 18 :Eu 2+ There are different afterglow curves under excitation light of different wavelengths, but the overall afterglow is not much different, indicating that the material has a large excitation range.

[0157] Experiment 6: The temperature dependence spectrum of the material prepared in Example 3 above is as follows Figure 8 As shown in the figure, under 365nm excitation, in a low temperature environment, as the temperature gradually rises from -120℃ to 230℃, the luminous intensity of the material changes very little. In particular, from low temperature to room temperature, the intensity change rate is only 0.3%.

[0158] Experiment 7: The material prepared in Example 3 was photographed at low temperature (the left picture is in a dark environment, the right picture is in a bright environment) and photoelectron signals were collected. Figure 9-10 As shown, the experiment confirms that the material has afterglow at -120°C.

[0159] The present invention has been described in detail with reference to the aforementioned embodiments. For those skilled in the art, it is still possible to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A low-temperature blue light long afterglow Mg2Al4Si5O 18 :X glass, characterized in that Its chemical formula is: Mg2Al4Si5O 18 :X,X=Eu 2+ ,Sm 3+ ,Tb 3+ ,Pr 3+ ,Er 3+ .

2. A Mg2Al4Si5O2 with low temperature blue light and long afterglow according to claim 1 18 : A method for preparing X glass, characterized in that: The following steps are involved: Step (a) Determine the mathematical relationship between reaction temperature and reaction time MgO, Al2O3, and SiO2 were mixed in a mass ratio of 1.1612:2.039:3.605, the weighed raw materials were put into a mortar, and ground to obtain a raw material mixed powder for preparing a matrix; The mixed powder of the raw materials of the parent body is placed in a reaction container as a reactant, and then the reaction container is placed in a microwave reaction device; The microwave reaction device was set to 100% power, and a time point was recorded every 2 minutes in the range of 1 to 25 minutes. When the reaction reached each time point, the core temperature of the reaction container was measured and recorded as the reaction temperature; With reaction temperature x as the abscissa and reaction time y as the ordinate, a fitting curve is obtained, and the expression of the fitting curve is: y=0.16904×exp(x / 181.79415)+0.63894; Step (ii): determine the rare earth ions to be doped and prepare the corresponding raw material mixed powder Select Eu 2+ ,Sm 3+ ,Tb 3+ ,Pr 3+ ,Er 3+ As a doping ion, prepare MgO, Al2O3, SiO2 and oxides corresponding to the doped rare earth ions, mix them according to the mass ratio of 1.1612:2.039:3.605:0.0500, grind the weighed raw materials to obtain raw material mixed powder; Step (iii): react according to the predicted reaction time According to the lowest phase transition temperatures of MgO, Al2O3, SiO2 and the oxides corresponding to the doping ions, the average value is calculated as the reaction temperature during the microwave preparation, and the corresponding reaction time is predicted according to the fitting curve obtained in step (i); The raw material mixed powder obtained in step (ii) is spread flat and placed in the middle and lower layer of the raw material crucible, and the raw material crucible is embedded in the carbon powder crucible, and then the carbon powder crucible is placed in the cavity formed by the heat-resistant brick body and the brick bottom, and the brick cover is closed and placed in a reaction microwave oven, and the carbon powder crucible is filled with activated carbon; the reaction is carried out according to the predicted reaction time, and after the reaction is completed, the low-temperature blue light long afterglow Mg2Al4Si5O 18 :XGlass.

3. The Mg2Al4Si5O2 with low temperature blue light and long afterglow according to claim 2 18 : A method for preparing X glass, characterized in that: In the step (a), the fitting curve is obtained by using the single exponential fitting method of nonlinear fitting in Origin.

4. The Mg2Al4Si5O2 with low temperature blue light and long afterglow according to claim 2 18 : A method for preparing X glass, characterized in that: In the step (ii), when the doped ion is Eu 2+ When the doped ion is Sm 3+ When the doped ion is Tb 3+ When the doped ion is Pr 3+ When the doped ion is Er 3+ When , the corresponding oxide is Er2O3.

5. The Mg2Al4Si5O2 with low temperature blue light and long afterglow according to claim 2 18 : A method for preparing X glass, characterized in that: The mesh size of the activated carbon particles in the step (iii) is 100-200 meshes.

6. The Mg2Al4Si5O2 with low temperature blue light and long afterglow according to claim 2 18 : A method for preparing X glass, characterized in that: In the step (iii), the mass ratio of the raw material mixed powder to the activated carbon is 1:

6.

7. The Mg2Al4Si5O2 with low temperature blue light and long afterglow according to claim 2 18 : A method for preparing X glass, characterized in that: In the step (iii), the reaction is carried out at a power of 600-1000 W according to the predicted reaction time.